Using neighborhood association area as new spatial data infrastructure to link public administrative data with GIS in Indonesia - Arip, Muriadi; Wanglin, Yan; Hirose, Kazuyo (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2019)
Despite its potential use for earth observation and GIS-based analysis, Public Administrative Database (PAD) has been neglected in the spatial big data discussions. For instance, linking unaggregated public databases to the smallest administrative units for mining spatial data currently absents from literatures. In this study, a neighbourhood association base map was developed and the usability as a platform for linking PAD in Indonesia was investigated. The base map is proposed as a new feature in the Indonesia’s SDI. A data model was developed, and data accuracy and reliability were assessed by a case study. Four unaggregated databases obtained from public institutions were examined using common structured query language. The results show that from 1.3 million records, more than 95% can be directly linked to the base map. Finally, it is concluded that despite existence of challenges, linking PAD with the base map is feasible and beneficial for GIS-based analysis.